Stimuli-Responsive Graphene Nanohybrids for Biomedical Applications - Dinesh K. Patel; Yu-Ri Seo; Ki-Taek Lim (Hindawi Limited, 2019)
Stimuli-responsive materials, also known as smart materials, can change their structure and, consequently, original behavior in response to external or internal stimuli. This is due to the change in the interactions between the various functional groups. Graphene, which is a single layer of carbon atoms with a hexagonal morphology and has excellent physiochemical properties with a high surface area, is frequently used in materials science for various applications. Numerous surface functionalizations are possible for the graphene structure with different functional groups, which can be used to alter the properties of native materials. Graphene-based hybrids exhibit significant improvements in their native properties. Since functionalized graphene contains several reactive groups, the behavior of such hybrid materials can be easily tuned by changing the external conditions, which is very useful in biomedical applications. Enhanced cell proliferation and differentiation of stem cells was reported on the surfaces of graphene-based hybrids with negligible cytotoxicity. In addition, pH or light-induced drug delivery with a controlled release rate was observed for such nanohybrids. Besides, notable improvements in antimicrobial activity were observed for nanohybrids, which demonstrated their potential for biomedical applications. This review describes the physiochemical properties of graphene and graphene-based hybrid materials for stimuli-responsive drug delivery, tissue engineering, and antimicrobial applications.